Karakteristik Pasien Relapse pada Pasien Skizofrenia dan Faktor Pencetusnya di Rumah Sakit Jiwa (RSJ) Provinsi Bali - Gemilang, Bintang Malam; Jaya Lesmana, Cokorda Bagus; Alit Aryani, Luh Nyoman (E-Jurnal Medika Udayana; Vol 6 No 10 (2017): E-Jurnal Medika Udayana, 2017)
Background: Schizophrenia is persisting psychotic disorder that need a long-term medication. There’s a remission period but positive symptoms tend to reemerge and ER is necessary. This study made to identify the prevalence of relapse and its triggering factor in the asylum of Bali. Method: 41 sample was taken from the medical record room in Asylum of Bali. The characteristic of patient taken from the ER report. The data then extracted into the, organized, and analyzed. Result: 41 sample acquired with gender comparison of man 61% and woman 39%. It is found that compliance to medication as a risk factor with the result of chi-square X2(1, N=38) = 7.057, P<0,05. The mean of shortest range between relapse is 410,9 days, and longest range between relapse is 1071,8 days. Negative corelation is found between the number of time relapse occurence and the range between relapse occurence with R(41)=0,210, P=0,226. Conclusion: In this study, 41 patients taken randomly. Compliance to medicine became one of the most important factor.The more relapse a experienced, the less time needed for reoccurence.